Anansi and the moss-covered rock - Kimmel, Eric A.; Stevens, Janet (New York : Holiday House, 1988)
Anansi the Spider uses a strange moss-covered rock in the forest to trick all the other animals, until Little Bush Deer decides he needs to learn a lesson.
Child Study Children's Book Committee
School Library Journal
Bulletin Of The Center For Children's Books
2.7
K-3
Keywords: Anansi (Legendary character); Anansi (Legendary character); Folklore; Anansi (Legendary character); Folklore